ANALISIS KUALITAS PELAYANAN UJI KIR KENDARAAN BERMOTOR DI DINAS PERHUBUNGAN SEMARANG - Nur Diana, Nabila; Santoso, R. Slamet; Subowo, Ari (Journal of Public Policy and Management Review, 2024)
The Motor Vehicle KIR Test Service is a series of activities to test and/or inspect motor vehicle parts or components organized by the Transportation Service, one of which includes the Semarang City Transportation Service. Motor Vehicle KIR Test Services need to be implemented to ensure technical safety, protect the environment from possible pollution, ensure that motorized vehicles in operation meet technical and roadworthiness requirements, thereby creating safe, comfortable, smooth and orderly land transportation. However, in practice, the Motor Vehicle KIR Test Service has not been implemented optimally. The aim of this research is to analyze the quality of Motor Vehicle KIR Test services at the Semarang City Transportation Department and related factors. This research uses descriptive qualitative methods with data collection techniques in the form of interviews, observation and documentation. The results of the research show that the Motor Vehicle KIR Test service at the Semarang City Transportation Department has been running well although deficiencies are still found in its implementation. Factors that influence the quality of Motor Vehicle KIR Testing services at the Semarang City Transportation Department are the regulatory system, organization and income.